Changing trends in reproductive/lifestyle factors in UK women: descriptive study within the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS). Issue 3 (6th March 2017) - Gentry-Maharaj, Aleksandra; Glazer, Clara; Burnell, Matthew; Ryan, Andy; Berry, Hannah; Kalsi, Jatinderpal; Woolas, Robert; Skates, Steve J; Campbell, Stuart; Parmar, Mahesh; Jacobs, Ian; Menon, Usha
Abstract : Objective: There has been considerable interest in the impact of reproductive factors on health but there are little data on how these have varied over time. We explore trends in reproductive/lifestyle factors of postmenopausal British women by analysing self-reported data from participants of the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS). Design: Prospective birth cohort analysis. Setting: Population cohort invited between 2001 and 2005 from age-sex registers of 27 Primary Care Trusts in England, Wales and Northern Ireland and recruited through 13 National Health Service Trusts. Participants: 202 638 postmenopausal women aged 50–74 years at randomisation to UKCTOCS between April 2001 and October 2005. Interventions: Women were stratified into the following six birth cohorts (1925–1929, 1930–1934, 1935–1939, 1940–1944, 1945–1949, 1950–1955) based on year of birth. Self-reported data on reproductive factors provided at recruitment were explored using tabular and graphical summaries to examine for differences between the birth cohorts. Outcome measures: Trends in mean age at menarche and menopause, use of oral contraceptives, change in family size, infertility treatments, tubal ligation and hysterectomy rates. Results: Women born between 1935 and 1955 made up 86% of the cohort. Median age at menarche decreased from 13.4 for women born between 1925 and 1929 to 12.8 for women born between 1950 and 1955. Increased use of the oral contraceptives, infertility treatments and smaller family size was observed in the younger birth cohorts. Tubal ligation rates increased for those born between 1925 and 1945, but this increase did not persist in subsequent cohorts. Hysterectomy rates (17–20%) did not change over time. Conclusions: The trends seen in this large cohort are likely to reflect the reproductive history of the UK female postmenopausal population of similar age. Since these are risk factors for hormone-related cancers, these trends are important in understanding the changing incidence of these cancers. Trial registration number: International Standard Randomised Controlled Trial Number: 22488978.